OFDM With Differential Index Modulation for Visible Light Communication - Di Zheng; Hongming Zhang; Jian Song (IEEE Photonics Journal)
In this paper, orthogonal frequency division multiplexing with differential index modulation (OFDM-DIM) is proposed for visible light communication. Compared with traditional OFDM with index modulation (OFDM-IM), the proposed scheme decreases the average number of used subcarriers when transmits the same amount of information bits, therefore higher spectral efficiency can be achieved. The simulation results present that OFDM-DIM can provide higher data transmission rate and lower bit error rate (BER) over additive white gaussian noise (AWGN) optical channel. Meanwhile, simulations over reference channels of short range optical wireless communication are implemented, where OFDM-DIM performances better than OFDM-IM when line-of-sight (LOS) components are dominant.